"Soldiering By Consent" and Military–Civil Relations: Military Transition Into the Public Space of Policing. (October 2019) - Murray, Emma; Taylor, Paul
Growth in the armed forces undertaking public policing is occurring in the United Kingdom and elsewhere, and as such, a complex security landscape emerges, both practically and conceptually. The aim here is to pose questions of the manifest and latent issues in the assemblage of multiple actors in public policing. It asks the reader to consider the implications of military actors transitioning from defense duties ordinarily associated with military work, to policing activities in public spaces. Taking the London 2012 Olympic Games as our point of reference, this article argues that to understand military presence, their role must be considered in the broader context of military and policing functions, the "war on terror, " accountability, and future priorities for public policing. We must be careful not to assign the presence of the military into preexisting understandings of how megaevents should be secured—the military patrolling the streets of London represents more. Instead, as their presence comes to be legitimate in certain geopolitical contexts, critical questions must be asked especially as public and private arrangements are continually reworked in the domestic fight against terrorism.